Application of Restorative Justice in Statutory Practice - Taufiqurokhman Taufiqurokhman; Dilla Hariyanti Tarigan; Danny Kunto Wibisono (Asian Journal of Social and Humanities, 2024)
The purpose of the research is to provide an explanation of how restorative justice is used in constitutional practice. In its implementation there has been development, due to awareness of the importance of restorative justice. So, the support of various parties, government, non-governmental organizations, civil society is needed so that restorative justice becomes an integral part of the Indonesian justice system in facing the challenges of law enforcement and constitutional practices which are explained in detail in the theory of Restorative Justice and the effectiveness of law enforcement. The research method was carried out normatively and sociologically with a descriptive analytical research design and using secondary and tertiary data to explain the writing of the research with the research locus in the Constitutional Procedural Law (HTN) courts. The findings of research on how restorative justice is used in constitutional practices can make law enforcement procedures that are inclusive, fair, and beneficial to society stronger. The utilization of supportive equity can assist with fortifying the groundworks of Indonesian state organization which depends on the standards of a vote based system, equity, and common liberties (HAM). The findings of the research lead to the following recommendations: (1) Indonesia must begin the process of developing a restorative justice law: (2) the government needs to increase the capacity of institutions and human resources involved in restorative justice; (3) it is necessary to collaborate with various parties to increase public awareness of the benefits of restorative justice (4) collaborate with various stakeholders to evaluate the restorative justice program.